Understanding walking and cycling. Summary of key findings and recommendations. - (:unkn) unknown (My University, 2011)
A wide range of both quantitative and qualitative data were collected in four English towns (Leeds, Leicester, Worcester, Lancaster), including a questionnaire survey, analysis of the built environment, interviews and ethnographies. Key findings of the research are that whilst attitudes to walking and cycling are mostly positive or neutral, many people who would like to engage in more active travel fail to do so due to a combination of factors. It is suggested that policies to increase levels of walking and cycling should focus not only on improving infrastructure (for instance through fully segregated cycle routes), but also must tackle broader social, economic, cultural and legal factors that currently inhibit walking and cycling. Together, such changes can create an environment in which driving for short trips in urban areas is seen as abnormal and walking or cycling seem the obvious choices.
Keywords: Individualverkehr; Fahrradverkehr; Verkehrspolitik; Fahrradnutzung; Radverkehrsförderung; Studie; Mobilitätshindernis; Mentalitätsveränderung; Handlungsempfehlung